Analisis Keputusan Investasi Karyawan Swasta di Kabupaten Jombang - Eka Megasari; Dhani Ichsanuddin Nur (Universitas Batanghari, 2022)
This study aims to determine how much influence the financial knowledge variable has on investment decisions, find out how much influence lifestyle variables have on investment decisions and find out how much influence income variables have on investment decisions for private employees in Jombang Regency. In this study using primary data types. The population in this study were private employees in Jombang Regency. While the sample in this study used a non-probability sampling technique. The method used in this study used a questionnaire with 100 respondents from private employees in Jombang Regency. The analytical tool used to test the hypothesis is Partial Least Square (PLS). To test the analysis of the research instrument using the outer model measurement with validity test and reliability test, and inner model measurement with R-square test, F-square test, and direct effect. The results of the analysis show that the financial knowledge variable can make a significant contribution in improving investment decisions, but the lifestyle variable cannot make a real contribution in improving investment decisions. While the income variable can provide a real contribution in improving investment decisions.